STRUCTURA ANATOMICĂ A LAMINEI FRUNZEI LA UNELE SPECII DE VIŢĂ DE VIE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2009)
The biometrical values of 13 anatomical characters of leaf lamina at 10 species of the genus Vitis L. are presented. The leaf’s adaxial epidermis is compound of a single polygonal cell row, varying by form and dimension, which are compactly arranged, closely one to another and does not stomata. The leaf’s abaxial epidermis is formed of basal epidermal cells, stomata, annex and auxiliary cells. The actinocyte type of stomatal complex is specifi c for the studied species. The density of leaf stomata characterizes every species and varies from 174 stomata/mm2 at the drought resistant species Vitis rupestris L. to 254 stomata/mm2 in the species of V.cinerea Arnold. The density of stomata and the stomatal index of studied species had greater values in the drought 2007 year. The greater thickness of leaf lamina, also of palisadic parenchyma and less area of leaf lamina too are thouse three morpho-anatomical characters which determine greater drought resistance of Vitis species and cultivars.